Cancer in Africa: The Untold Story - Hamdi, Yosr; Abdeljaoued-Tej, Ines; Zatchi, Afzal Ali; Abdelhak, Sonia; Boubaker, Samir; Brown, Joel S.; Benkahla, Alia (Frontiers in Oncology, 2021)
Background: Despite rising incidence and mortality rates, cancer has been given low priority in the research field and in healthcare services. Indeed, 57% of all new cancer cases around the world occur in low income countries exacerbated by lack of awareness, lack of preventive strategies, and increased life expectancies. Despite recent efforts devoted to cancer epidemiology, statistics on cancer rates in Africa are often dispersed across different registries. In this study we aimed to collate and analyze the incidence and fatality rates for the 10 most common and fatal cancers in 56 African countries from 5 different African regions (North, West, East, Central and South) over 16-years (2002–2018). Analysis are performed by gender, by the Human Development Index, and by the number of medical devices. Results: We classified the 10 studied cancers into 3 categories based on their risk factors: genetics, environmental/lifestyle and infectious-disease linked cancers. Northern and Southern Africa were most similar in their cancer incidences and fatality rates compared to other African regions. The most prevalent cancers are breast, bladder and liver cancers in Northern Africa; prostate, lung and colorectal cancers in Southern Africa, and esophageal and cervical cancer in East Africa. In Southern Africa, fatality rates from prostate cancer and cervical cancer have increased. In addition, these three cancers are less fatal in Northern and Southern Africa compared to other regions, which correlates with the Human Development Index and the availability of medical devices. With the exception of thyroid cancer, our results showed that all remaining cancers have higher incidences in males than females. Conclusion: Our results showed that the African continent suffers from a shortage of medical equipment, research resources and epidemiological expertise. We see a need for implementing more accurate preventive strategies to tackle this disease as many cases are likely preventable. Opportunities exist for vaccination programs for cervical and liver cancer, genetic testing and use of new targeted therapies for breast and prostate cancer, and positive changes in lifestyle for lung, colorectal and bladder cancers. Such recommendations should be tailored for the different African regions depending on their disease profiles and specific needs.